2015
DOI: 10.1371/journal.pone.0135061
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Structured HIV Epidemic in Israel: Roles of Risk and Ethnicity

Abstract: BackgroundHIV in Israel started with a subtype-B epidemic among men who have sex with men, followed in the 1980s and 1990s by introductions of subtype C from Ethiopia (predominantly acquired by heterosexual transmission) and subtype A from the former Soviet Union (FSU, most often acquired by intravenous drug use). The epidemic matured over the last 15 years without additional large influx of exogenous infections. Between 2005 and 2013 the number of infected men who have sex with men (MSM) increased 2.9-fold, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…Our analysis showed that there were multiple introductions of subtype B into Bulgaria from at least 8 different countries, which then spread amongst Bulgarians, including within three large clusters with 14, 67, and 552 Bulgarian members. Interestingly, HIV-1 subtype B sequences from Israel from 2005-2013 were frequently associated with Bulgarian sequences in our study [39]. Most subtype B-infected participants in that study were Israeli-born (73%), reporting high MSM exposure (83%) and suggesting possible MSM interactions between Israel and Bulgaria.…”
Section: Discussionmentioning
confidence: 48%
“…Our analysis showed that there were multiple introductions of subtype B into Bulgaria from at least 8 different countries, which then spread amongst Bulgarians, including within three large clusters with 14, 67, and 552 Bulgarian members. Interestingly, HIV-1 subtype B sequences from Israel from 2005-2013 were frequently associated with Bulgarian sequences in our study [39]. Most subtype B-infected participants in that study were Israeli-born (73%), reporting high MSM exposure (83%) and suggesting possible MSM interactions between Israel and Bulgaria.…”
Section: Discussionmentioning
confidence: 48%
“…Association between MSM transmission route and clustering within the subtype B infected cases has been previously reported in various cohorts [ 18 , 19 , 25 , 36 , 37 , 38 ]. Clinical characteristics of the clustered sequences followed the patterns observed in other studies including lack of prior antiretroviral treatment exposure, higher CD4 lymphocyte counts, earlier stage of HIV disease and more recent sampling [ 16 , 21 ].…”
Section: Discussionmentioning
confidence: 88%
“…This is consistent with the identification of large, interregional clusters in our analysis including the ones comprising of 13 and 20 sequences. These large clusters may reflect rapidly growing sub-epidemics [ 19 ] and have been found throughout subtype B infected populations worldwide [ 38 , 42 , 43 , 44 , 45 ], however the exact transmission pattern within the transmission clusters is difficult to analyze in the cohort of chronically infected individuals. As expansion of the clusters over time has been reported [ 19 , 46 ] this finding supports the need for early introduction of antiretroviral therapy in populations with frequent clustering aiming to break the transmission chains [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subtype C was predominant (89%) in people emigrating from Africa, considered as those originating from counties with generalized HIV epidemics (OGE). Subtype A was prevalent (71%) among HIV-1-infected persons coming from the former USSR [ 13 ].…”
Section: Introductionmentioning
confidence: 99%